1990
DOI: 10.1002/bies.950121004
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair in mammalian cells

Abstract: A vital process in maintaining a low genetic error rate is the removal of mismatched bases in DNA. The importance of this process in E. coli is demonstrated by the 100-1000 fold increase in mutation frequency observed in cells deficient in this repair system. Mismatches can arise as a consequence of recombination, errors in replication and as a result of spontaneous chemical deamination, the latter process resulting in an estimated twelve T:G mismatches per genome per day in mammalian cells. Recent studies, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 36 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Others have suggested that nicks may improve the repair efficiency and the repair is initiated from the nick [Thomas et al 1991;Holmes et al 1990;Fang and Modrich 1993;Umar et al 1994;Miller et al 1997;Taghian et al 1998]. Conflicting studies in monkey COS-7 (CV-1 in Origin and carrying the SV40 genetic material) cells suggested that nicks did not have an effect in directing the strand repair [Heywood and Burke 1990a;1990b]. Additional studies supported this by showing equal mismatch repair efficiency with nicked and intact plasmid DNA in in vivo studies [Lei et al 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that nicks may improve the repair efficiency and the repair is initiated from the nick [Thomas et al 1991;Holmes et al 1990;Fang and Modrich 1993;Umar et al 1994;Miller et al 1997;Taghian et al 1998]. Conflicting studies in monkey COS-7 (CV-1 in Origin and carrying the SV40 genetic material) cells suggested that nicks did not have an effect in directing the strand repair [Heywood and Burke 1990a;1990b]. Additional studies supported this by showing equal mismatch repair efficiency with nicked and intact plasmid DNA in in vivo studies [Lei et al 2004].…”
Section: Discussionmentioning
confidence: 99%